Determination of Soil Cadmium Threshold for Potato - Li, Wei; He, Xue; Zhang, Jie; Liu, Ke (Frontiers in Environmental Science, 2022)
In this study, pot experiments were conducted to investigate the characteristics of Cd transfer to potato tubers from two types of soil. The results showed that the Log-normal and Burr III functions can be used to determine the sensitivity of different potato varieties to Cd as well as the soil Cd threshold. With regard to the prediction accuracy, the root mean squared error (RMSE) values for the total Cd biaoaccumulation factor (BAFtotal) calculated with both functions were smaller than those for exogenous Cd biaoaccumulation (BAFadd) in acidic and alkaline soils, indicating that BAFtotal is more appropriate for the calculation of the soil Cd threshold. The average Cd threshold values in acidic soil calculated with the Log-normal and Burr III functions were 0.411 and 0.461 mg kg−1, and the average values in alkaline soil were 0.716 and 0.888, respectively. The Log-normal function can also be applied to fit the sensitivity distributions of different species for the development of appropriate soil Cd threshold values for conservation purposes.